2020
DOI: 10.1021/acs.langmuir.0c01771
|View full text |Cite
|
Sign up to set email alerts
|

Possibility of Obtaining Two Orders of Magnitude Larger Electrokinetic Streaming Potentials, through Liquid Infiltrated Surfaces

Abstract: A methodology for substantially increasing the magnitude of the electrokinetic streaming potential (Vs) from ~ 0.02 V to as large as ~ 1.6 V is proposed. This is done through deploying textured, liquid-filled surfaces (LFS), filled with low viscosity oils, for electrolyte flow. The charge density at the electrolyte-oil interface as well as the enhanced slip may be responsible for enhancement of the Vs. It was found, through experimental analysis as well as computational simulations, that the fluid slip length … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…7,13 While a high b is hence desirable for a large V s , the conventional method through which SH surfaces are synthesized involves air-filled pockets. Related to this context, liquid-filled surfaces (LFS) were proposed 13,18,19 for optimizing the electrokinetic characteristics. Here, an electrolyte-immiscible oil was infiltrated into patterned surface grooves and the electrolyte flow over the LFS indicated a reduced b as well as an amplified ζ.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,13 While a high b is hence desirable for a large V s , the conventional method through which SH surfaces are synthesized involves air-filled pockets. Related to this context, liquid-filled surfaces (LFS) were proposed 13,18,19 for optimizing the electrokinetic characteristics. Here, an electrolyte-immiscible oil was infiltrated into patterned surface grooves and the electrolyte flow over the LFS indicated a reduced b as well as an amplified ζ.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Related to this context, liquid-filled surfaces (LFS) were proposed ,, for optimizing the electrokinetic characteristics. Here, an electrolyte-immiscible oil was infiltrated into patterned surface grooves and the electrolyte flow over the LFS indicated a reduced b as well as an amplified ζ.…”
Section: Introductionmentioning
confidence: 99%
“…a) Distribution of materials used in applications. [ 10,12–16,19,20,22–27,30,31,33–40,44–48,53–55,64–80,82–108,117–123 ] b) Output voltage and power density for different materials. c) The output voltage and d) averaged voltage of single and integrated devices.…”
Section: Methodsmentioning
confidence: 99%
“…23,24 In contrast to the typical air-filled surfaces (AFS), alternate liquid filled surfaces (LFS) were fabricated by replacing the air with aqueous electrolyte immiscible oil (with a finite electrical potential) and generated a larger V s . 25,26 In such LFS, the infiltrated oil has been shown to be stable, and the LFS has been shown to maintain an intact surface over a range of pressures applied to the electrolyte flow channel. 27,28 It was also shown that there is negligible shear-induced drainage under external flow.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Therefore, a balance of b and ζ needs to be considered to obtain a higher V s . Filling air gaps or infiltrating pores with liquid to form a solid–liquid composite surface was suggested as one feasible methodology to achieve such a balance. , In contrast to the typical air-filled surfaces (AFS), alternate liquid filled surfaces (LFS) were fabricated by replacing the air with aqueous electrolyte immiscible oil (with a finite electrical potential) and generated a larger V s . , In such LFS, the infiltrated oil has been shown to be stable, and the LFS has been shown to maintain an intact surface over a range of pressures applied to the electrolyte flow channel. , It was also shown that there is negligible shear-induced drainage under external flow . The orientational effects on such liquid filled patterned surfaces, manifested through a tensorial aspect to the developed V s , were considered. , It was indicated through such experiments that ζ might contribute more to V s generation compared to the slip.…”
Section: Introductionmentioning
confidence: 99%